How energy transition will affect electricity prices in Serbia? - Nikolic, Ivan; Filipović, Sanja (Industrija, 2020)
The aim of this paper is to give an answer on question does it energy transition will have an effect on electricity prices in Serbia. As a part of the Energy Community, Serbia is oblidged to harmonize its energy regulation with the Europan Union. Even though electricity price in Serbia is the lowest in Europe, it has a high share in the household consumer basket. However, electricity price does not include the cost of CO2 emissions. The recent adoption of National Emission Reduction Plan implies Serbia’s obligation to reduce emissions from large combustion plants by 2028. This commitment will entail significant investments and will influence the further development of the electricity sector. Accession of the Republic of Serbia to the EU and consequent implementation of EU ETS in the period 2023-2028, will have a significant impact on the EPS electricity cost production. At the moment, rough estimates show that this amount goes up to 2.5 euro cents per kWh produced by thermal power plants.